Integration of Cadmium Accumulation, Subcellular Distribution, and Physiological Responses to Understand Cadmium Tolerance in Apple Rootstocks - Zhou, Jiangtao; Wan, Huixue; He, Jiali; Lyu, Deguo; Li, Huifeng (Frontiers in Plant Science, 2017)
Cadmium (Cd) is a nonessential and highly toxic element causing agricultural problems. However, little information is available about the variation in Cd tolerance among apple rootstocks and its underlying physiological regulation mechanisms. This study investigated Cd accumulation, subcellular distribution and chemical forms as well as physiological changes among four apple rootstocks exposed to either 0 or 300 μM CdCl2. The results showed that variations in Cd tolerance existed among these rootstocks. Cd exposure caused decline in photosynthesis, chlorophyll and biomass in four apple rootstocks, which was less pronounced in M. baccata, indicating its higher Cd tolerance. This finding was corroborated with higher Cd tolerance indexes (TIs) of the whole plant in M. baccata than those in the other three apple rootstocks. Among the four apple rootstocks, M. baccata displayed the lowest Cd concentrations in roots, wood and leaves, the smallest total Cd amounts as well as the lowest BCF. In apple rootstocks, it was found that to immobilize Cd in cell wall and soluble fraction (most likely in vacuole) and to convert it into pectate- or protein- integrated forms and undissolved Cd phosphate forms may be the primary strategies to reduce Cd mobility and toxicity. The physiological changes including ROS, carbohydrates and antioxidants were in line with the variations of Cd tolerance among four apple rootstocks. In comparison with the other three apple rootstocks, M. baccata had lower concentrations of ROS in roots and bark, H2O2 in roots and leaves and MDA in roots, wood and bark, but higher concentrations of soluble sugars in bark and starch in roots and leaves, and enhanced antioxidants. These results indicate that M. baccata are more tolerant to Cd stress than the other three apple rootstocks under the current experiment conditions, which is probably related to Cd accumulation, subcellular partitioning and chemical forms of Cd and well-coordinated antioxidant defense mechanisms.